Gender-specific characteristics of hypertrophic response in cardiomyocytes derived from human embryonic stem cells - Shiva Ahmadvand; Ali Osia; Anna Meyfour; Sara Pahlavan (Journal of Cardiovascular and Thoracic Research, 2021)
Introduction: Gender-specific phenotypes of the heart were reported with respect to both physiology and pathology. While most differences were associated with the sex hormones, differential expression of genes received special attention, particularly X-Y chromosomes’ genes. Methods: Here, we compared cardiogenesis by gene expression analysis of lineage specific markers and X-Y chromosomes’ genes, during in vitro differentiation of XY and XX human embryonic stem cells (hESC), in a hormone-free setup. Results: Downregulation of pluripotency marker (NANOG) and upregulation of cardiac mesoderm and progenitor markers (GATA4, TBX5, NKX2.5, ISL1) was remained temporally similar in differentiating XY and XX hESCs. Isoproterenol treatment of XY and XX hESC-derived cardiomyocytes (hESCCM) induced hypertrophy in a sex-specific manner, with female cardiomyocytes showing response at higher isoproterenol concentration and a later time point of differentiation. Interestingly, KDM5C as an X-linked gene, was markedly upregulated in both hypertrophied male and female cardiomyocytes. Conclusion: Collectively, our results indicated a temporally identical cardiogenesis, but more susceptibility of XY hESC-CM to hypertrophic stimulus in a hormone-free condition.